Defect source location of a natural defect on a high speedrolling element bearing with Acoustic Emission - Eftekharnejad, Babak; Addali, Abdulmajid; Mba, David (PHM Society, 2011)
The application of Acoustic Emission (AE) technology for machine health monitoring is gaining ground as powerful tool for health diagnosis of rolling element bearings. The successful application of AE to life prognosis of bearings is very dependent on the ability of the technology to identify and locate a defect at its earliest stage. Determining source locations of AE signals originating in real time from materials under load is one of the major advantages of the technology. This paper presents results which highlight the ability of AE to locate naturally initiated defects on high-speed roller element bearing in-situ. To date such location has only be successfully demonstrated at rotational speeds of less than 100 rpm.
Proceedings of the Annual Conference of the PHM Society 2011
Keywords: condition monitoring; acoustic emission; Bearing; Source Location